Irisan Penguasan Negara dan Desentralisasi dalam Prospek Pengaturan Energi Terbarukan di Indonesia: Irisan Penguasan Negara dan Desentralisasi dalam Prospek Pengaturan Energi Terbarukan di Indonesia - Muhammad RM Fayasy Failaq; Nusantara, Irma Aulia Pertiwi (Jurnal Konstitusi, 2024)
Renewable energy has great potential in Indonesia, but Indonesia does not have integrated regulations related to renewable energy considering that these regulations are still in the process of the 2022 Proleges Draft Law (RUU). This research aims to outline views on renewable energy through the concept of central and regional government authority in managing renewable energy and analyzing it through the prospects for state control and decentralization, in order to see the potential readiness of regions in Indonesia. This research was conducted using normative juridical research. The results of this research show that the concept of state control has an intersection with decentralization in the management of energy resources. Indonesia has enormous potential for renewable energy, but regions in Indonesia still have challenges regarding readiness. Therefore, it is necessary to accelerate the EBT Bill as a legal basis to support the acceleration of renewable energy in Indonesia and the importance of carrying out the five functions of state control based on decentralization ideally for the development of renewable energy.